„Я люблю ездить в г. Челябинск и в Польшу”: Nikolaj Kolada i Polacy – wzajemne fascynacje - Sadowska, Monika (Acta Polono-Ruthenica, 2018)
Nikolai Kolada’s, by critics called also the “Almodovar of Russian theatre”, artistic work for years is very popular in Poland. This article is an attempt to present the profile of Nikolai Kolada and chosen aspects of his literary output and dramatist’s works reception in Poland. The author also tries to put attention to “father’s of new Russian dramaturgy” cooperation with representatives of Polish theatrical environment and to solve the secret of his popularity in Poland phenomenon.